(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2024)
Memory impacts every aspect of life: our sense of self, our knowledge of suffering (our own and the suffering of others), the search for meaning, the formation of community. The study of memory has long fascinated psychologists, historians, doctors, and philosophers, all of whom work to uncover the meaning behind the act of remembering. In reflecting on what it means to be human, we cannot ignore the vital role that memory plays in shaping the self and defining humans’ collective life. This essay explores the complexities of memory, both the individual and the collective, and then translates the research into a print. The combination of art and writing speaks to the dual nature of memory, as it can be changed and shared through time. For additional context, listen to the author’s reflection on the piece below.